Pengaruh kualitas produk dan harga terhadap keputusan pembelian konsumen pada UD. Pleximo penjual sepatu di Kota Tangerang - Noviyanti, Iis; Rosalina, Eti (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the effect of product quality on purchasing decisions, determine the effect of price on purchasing decisions. And knowing the effect of product quality and price on purchasing decisions at UD. Pleximo. The method of this research is quantitative associative method. The population in this study is the consumer retailer UD. Pleximo totaling 430, the sampling technique in this study used the solvin formula and a sample of 82 respondents was obtained. The data collection method used is distributing questionnaires and using a Likert scale. The results of the study show that product quality and price have a very strong relationship with product purchasing decisions at UD Pleximo. The calculation of the coefficient of determination (R2) yields 0.704. This shows that the influence of product quality and price on consumer purchasing decisions is 70.4 percent, while 29.6 percent is influenced by other factors. So that product quality and price have a significant effect and have a simultaneous positive direction on purchasing decisions, which means that product quality and prices offered by UD Pleximo Tangerang City play a very important role in attracting consumers to shop for shoes at UD Pleximo Tangerang City.